Analisis Erosi Dan Sedimentasi Sungai Siak Menggunakan Data Satelit - Harto, Galuh Rio; Siswanto, Siswanto; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Siak River as one of four big rivers in Riau Province has morfology condition of meanders which caused erotion. The process of soil erotion on river edge happened due to the process of erotion that occured constantly on the bed of the edge as a reaction of river bed changes towards the condition of flow pattern on meanders. This research is aimed to identify the erotion and sedimentation on Siak River based on affecting parameters by conducting analysis using satelite data and comparing the water elevations which are similar or having the least elevation different.Based on the research, the biggest area of erotion occured on condition 1 of middle downstream between 2000-2013 with the value of erotion area of 574132.6 m or 57.41 ha and the biggest area of sedimentation occured on condition 1 of end downstream between 2000-2013 with the value of sedimentation area of 953738.2 m or 95.37 ha.Keywords : river, erotion, sedimentation, daily water level elevation, satellite data.